A novel automated magnetic resonance image segmentation approach based on elliptical gamma mixture model for breast lumps detection. Issue 4 (26th May 2019) - Biswas, Biswajit; Ghosh, Swarup Kr; Ghosh, Anupam
Abstract: This article introduces a novel semisupervised automated segmentation approach for breast magnetic resonance (MR) image on multicore CPU‐GPU systems. The basic idea of the proposed method is clustering‐based semisupervised classifier devised by elliptical gamma mixture model (EGMM). Parameters of EGMM are identified by the iterative log‐expectation maximization (EM) algorithm. The suggested classifier labels the groups of voxels in an input image first and then classifies the image slices using the EGMM. Two different implementations of the proposed algorithm have been developed based on two different types of high‐performance computing architectures such as graphics processing units (GPUs) and multicore processors. To realize the real‐time segmentation performance of our algorithm with two distinctive architecture, we have tested a set of breast MR images collected from MedPix. Comparison between two architectures in terms of segmentation performance and computational cost is assessed by the analysis of simulation and experimental results.